Effect of Proprioceptive Neuromuscular Facilitation (PNF) on Muscle Strength in Post-Stroke Patients - Syokumawena Syokumawena; Sumitro Adi Putra; Rumentalia Sulistini; Wahyu Dwi Ari Wibowo; Efa Trisna (GLOBAL HEALTH SCIENCE GROUP, 2024)
Post-stroke rehabilitation often involves improving muscle strength and motor function to enhance the quality of life for stroke survivors. Proprioceptive Neuromuscular Facilitation (PNF) has emerged as an effective therapy in this context, particularly in enhancing muscle strength and upper limb function. PNF techniques use specific patterns of movement to activate proprioceptors and improve muscle coordination, which may aid in recovery for stroke patients. Despite its potential, limited research has evaluated its impact on muscle strength improvement, making this study significant.Research Objective: The primary aim of this study was to assess the effectiveness of Proprioceptive Neuromuscular Facilitation (PNF) in improving muscle strength in post-stroke patients, with a focus on the upper limbs. The research was conducted to evaluate the pre-test and post-test muscle strength scores, and to analyze the impact of PNF on muscle strength recovery.Research Methods: This research employed a pre-experimental design with a one-group pre-post test. A sample of 34 post-stroke patients was selected using purposive sampling from the Merdeka Health Center and 1 Ulu Palembang, South Sumatra, Indonesia. The intervention consisted of PNF exercises conducted three times a week for three months. Muscle strength was measured using a hand dynamometer both before and after the intervention. Statistical analysis using Cohen’s d and paired t-tests was performed to evaluate the effectiveness of the intervention.Results: The results revealed a significant improvement in muscle strength after PNF intervention. The mean muscle strength score increased from 2.50 ± 0.570 (pre-test) to 3.64 ± 0.570 (post-test), with a difference of 1.14 ± 0.570. Cohen’s d coefficient of 2 indicated a large effect size, confirming substantial improvement. The paired t-test yielded a p-value of 0.001, demonstrating that the changes were statistically significant.Conclusion: Proprioceptive Neuromuscular Facilitation (PNF) significantly improves muscle strength in post-stroke patients, particularly in the upper limbs.